Information and Empowerment of Families of Children With Cerebral Palsy in Brazil: The Knowledge Translation Role of Nossa Casa Institute - Airoldi, Marina J.; Vieira, Beatriz S.; Teplicky, Rachel; Chalfun, Deborah; Bonfim, Rafael G. A. S.; Mancini, Marisa C.; Rosenbaum, Peter; Brandão, Marina B. (Frontiers in Rehabilitation Sciences, 2021)
Knowledge translation (KT) is gaining attention in the pediatric rehabilitation field. Nossa Casa Institute is the first organization in Brazil aiming to promote cerebral palsy (CP) awareness and empower families by discussing reliable information. Our main goal is to build a network where individuals with CP and their families, researchers, health care professionals and services could communicate and share experiences. In this article, we describe the experience of planning and conducting an educational, interactive, online workshop to foster principles of family-centred service (FCS). We used the action cycle from the Knowledge to Action framework to describe and ground the proposed activities. In Module 1, Challenges and barriers to incorporate family-centred principles, we discussed the historical perspective, main principles and challenges related to FCS implementation. Module 2, What is my contribution to the family-centred service? was aimed to foster strategies to improve the implementation of principles of FCS in the care of children with disabilities. In Module 3, What can we do together? the groups presented their ideas and suggestions. This interactive and educational workshop was an opportunity for Nossa Casa Institute to disseminate accessible and reliable information regarding FCS, and to empower families to participate actively in the rehabilitation process and advocate for the best provision of care for their children. Future actions of Nossa Casa Institute include the coordination of a national conference to connect families, individuals with CP, healthcare and rehabilitation professionals, and researchers.